Sosialisasi Keagamaan: Menjadi Pendidik yang Qur'ani sebagai Langkah Awal Menanamkan Karakter Baik pada Siswa - Pertiwi, Novia Ayu Sekar; Prihatiningtyas, Suci; Efendi, Basthomi; Chudloifah, Chudloifah; Robbainah, Sofi Inayatur; Hidayat, Mohammad Muchsin (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Dukuhdimoro Village in East Java is home to various educational and religious institutions. However, the challenge lies in shaping the character of the younger generation due to a lack of guidance and role modeling from educators. To address this issue, community service activities are conducted with social and psychological approaches. One of the focuses is Quranic character education for educators to integrate religious values into teaching. Evaluations show an improvement in educators' understanding of the Quranic generation concept. The pocketbook